High-K ('propeller') states in the infrared spectrum of the Ar-CO complex - Xu, Yunjie; Civiš, S.; McKellar, A.R.W.; König, S.; Haverlag, M.; Hilpert, G.; Havenith, M. (Molecular physics, 1996)
The infrared spectrum of the weakly bound complex Ar-CO has been studied in the 4·7 μm region of the CO stretching vibration by means of three complementary techniques: a continuous slit-jet supersonic expansion with a tunable diode laser, a long-path cooled cell with a tunable diode laser, and a long-path cooled cell with a Fourier transform infrared spectrometer. Previous studies have characterized states of Ar-CO with K a values up to 3 in the ground bending state, and up to 1 in the first excited bending state. Here these studies are extended up to K a = 6 by analysing subbands with K a = 4 ← 3, 3 ← 4, 5 ← 4, and 6 ← 5, and thereby obtaining subband origins, rotational parameters, and centrifugal distortion parameters which characterize these states. The results illustrate the relative stability and regularity of high-K (propeller) states, even if on close examination they are subject to perturbations, as compared with excited bending (windmill) and van der Waals stretching states in weakly bound T-shaped complexes.